A novel hierarchical distributed framework for optimal reactive power dispatch based on a system of systems structure. (September 2019) - Hashemi, Mohamadreza; Zarif, Mohammad Haddad
Abstract: Optimal reactive power dispatch is one of the major issues in operation of power systems which aims to minimize losses, voltage stability, voltage deviation, etc. through an optimal adjustment of control variables. Recently, some alterations have been involved in control procedures, management and scheduling of these systems due to the power systems restructure, electricity markets and smart grids. These changes are notable in methods used for optimal dispatch of reactive power as well. According to the hierarchical structure of the power grids, this paper presents a hierarchical distributed framework based on a System of Systems (SoS) concept. In this structure, every section of the grid is controlled by a smart agent. Agents are interconnected and exchange the required data via a telecommunication network. In this paper, the amounts of active and reactive power exchanged between agents are considered as boundary and common parameters. Our proposed method is implemented on the IEEE 118-bus network connected to 7 active power distribution networks. The results are compared to the ones obtained from a distributed method based on an Incident Command System (ICS) and a centralized control method. It turns out that the proposed method outperforms the other two competing methods.